Hubungan Kepatuhan dalam Kunjungan Posyandu Terhadap Status Gizi Balita di Desa Mlilir Kecamatan Bandungan Kabupaten Semarang - Karimatul Hilmiyah; Luvi Dian Afriyani (Indonesian Journal of Midwifery (IJM), 2018)
The cases of malnutrition in Indonesia are still very high at 1.1 million toddler from 21,436,940 in the number of toddler who are registered in Pediatric Healthcare. The village of Mlilir in the Public Health Center Jimbaran in the last three months had increase for the number of malnutrition for toddler. Efforts to prevent the problems of nutrition toward toddler are participating in Pediatric Healthcare activities. The obedience in visits to each Pediatric Healthcare activity will certainly affect the nutritional status of the toddler. Because one of the objectives of Pediatric Healthcare Â is to monitor the improvement of nutritional status of toddler.This research aimed to analyze the relation of the obedience Pediatric Healthcare visit toward toddler nutrition status. This research used a quantitative design analytic survey with a Case Control approach. The population in this research was all the mothers who had children aged 12-59 months in Mlilir Village, Bandungan district, Semarang Regency in April 2018, 242 respondents. Case samples used were taken with accidentall sampling technique, 18 respondents and control samples using matching sample technique, in the education and occupation of mothers around 36 respondents with a ratio of 1: 2. The results of the study using the chi square test showed , there was a relationship between obedience in the Pediatric Healthcare visit to the nutritional status of toddler.There was a relationship between obedience in Pediatric Healthcare visits to the nutritional status of toddler.Health workers provide media counseling that can be brought home like leaflets so that the information is reachable to the parents of the toddler.